ANALYSIS OF HALAL LABELLING TOWARDS PURCHASE QUANTITY AND CONSUMER SATISFACTION IN MAOMAO (THAI TEA) - Atieq, Muhammad Qoes; Rizqi, Egin Goniyatur; Sindu, Rohani (IAIN Manado, 2020)
The development of halal industry is growing rapidly in various sectors so that it becomes a trend of human lifestyle throughout the world. Maomao (Thai Tea) is one of the UMKM that has not been certified as halal, which sells beverage products made from raw tea of Thailand that is rife among the public and is able to spread outlets quickly and broadly in the three regions of Cirebon. In this, case it is interesting to study consumer awareness of halal labels on food and beverages. The research conducted by the author aims to determine the effect of halal labeling on the quantity of purchase and customer satisfaction at Maomao UMKM in Cirebon City. The author uses research methods with a qualitative approach and descriptive analysis as well as approaches from various sources of literature, such as books, journals, reports, and previous reports on research outcomes. Based on the research carried out, according to the author's analysis halal labeling on Maomao (Thai Tea) does not affect the level of purchase and customer satisfaction. Because the majority of consumers have believed that Maomao (Thai Tea) has guaranteed halal for the product. This is known from the ingredients in producing Maomao (Thai Tea) (although for the Maomao brand itself has not been certified as halal) and hygienic manufacturing procedure. Through this paper, it is expected that the government or related parties to facilitate the process of halal certification, so that the businessmen prioritize halal labels on their products.